Electrophysiological Characteristics in Depressive Personality Disorder: An Event-Related Potential Study - Yu, Hong-Hua; Gu, Si-meng; Yao, Fang-Min; Wang, Zhi-Ren; Fu, Wen-Qing (Frontiers in Psychology, 2019)
This study aimed to investigate the neurophysiological characteristics of young people with depressive personality disorder using event-related potentials (ERP). To explore the effects of visual-emotional words on ERP, mainly N350, we recruited 19 individuals with depressive personality disorder and 10 healthy controls. ERP were recorded while the subjects performed decisions on target words that were classified into three categories: emotionally positive, negative, and neutral. The ERP signals were then separately averaged according to the subjects’ classifications. Data analysis showed that the amplitude of N350 was larger in response to positive and negative words than to neutral words. The latency of N350 was longer in negative words, in contrast to positive and neutral words. However, no difference was found between the two groups. These results suggest that neurophysiological characteristics of young people with depressive personality disorder in visual-emotional word processing have not yet been influenced by their personality traits. To some extent, N350 reflected semantic processes and was not sensitive to participants’ mood state. Keywords: Depressive Personality Disorder; Event related potential; N350; Emotion; word classification Acknowledgments This work was supported Beijing Municipal Science and Technology Project (Z181100001518005). Number of words: 4979; Number of figures: 4